2019
DOI: 10.3390/ijms20225636
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Molecular Mechanism underlying the Stable Purple-Red Leaf Phenotype in Lagerstroemia indica cv. Ebony Embers

Abstract: Lagerstroemia indica is an important ornamental tree worldwide. The development of cultivars with colorful leaves and increased ornamental value represents one of the current main research topics. We investigated the anthocyanin profiles in two contrasting cultivars for leaf color phenotypes and explored the underlying molecular basis. Both cultivars display purple-red young leaves (Stage 1), and when the leaves mature (Stage 2), they turn green in HD (Lagerstroemia Dynamite) but remain unchanged in ZD (Lagers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Variation of anthocyanin content in plant tissues is ascribed to the differential expression levels of key genes participating in the biosynthetic pathway [51]. Comparison of cultivars with contrasting fruit flesh colors allowed us to identify differentially expressed anthocyanin biosynthetic genes that may affect the color formation as previously documented in turnip [52], Prunus mira [53] and Lagerstromemia indica [54]. Interestingly, 12 key genes were highlighted in this study, seven of which directly involved in the anthocyanin biosynthetic pathway, were found significantly higher expressed in the colored cultivars (red and pink) as compared to the white cultivar.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Variation of anthocyanin content in plant tissues is ascribed to the differential expression levels of key genes participating in the biosynthetic pathway [51]. Comparison of cultivars with contrasting fruit flesh colors allowed us to identify differentially expressed anthocyanin biosynthetic genes that may affect the color formation as previously documented in turnip [52], Prunus mira [53] and Lagerstromemia indica [54]. Interestingly, 12 key genes were highlighted in this study, seven of which directly involved in the anthocyanin biosynthetic pathway, were found significantly higher expressed in the colored cultivars (red and pink) as compared to the white cultivar.…”
Section: Discussionmentioning
confidence: 93%
“…Predicting the specific target genes of these MYB and bHLH TFs would facilitate the selection of candidate genes to target for controlling flesh color in Hylocereus spp. As proposed by Qiao et al [54], the construction of gene co-expressed networks connecting the candidate regulators and their targets could be an effective approach.…”
Section: Discussionmentioning
confidence: 99%
“…Another similar study showed that the content of 7 anthocyanins in red leaf were higher than that in green leaf, and 19 key MYB regulators were co-expressed with the avonoid-anthocyanin biosynthetic genes in leaf color formation of Lagerstroemia indica cv. Ebony Embers [27]. The changes of avonoid related metabolites, enzyme activity and gene expression in the leaves color development of Cymbidium sinense 'Red Sun' were detected via metabolome.…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids give yellow to red color to fruits and have scope to serve as natural colorants in food industry [6,18]. The biosynthetic pathway of anthocyanins is well studied in different plants and is regulated by several key genes and regulatory factors [19,20]. However, very few studies were conducted to study the betalains biosynthesis pathway and their regulatory genes because they are present only in single plant order, namely, Caryophyllales [6].…”
Section: Introductionmentioning
confidence: 99%